2005
DOI: 10.1038/sj.cr.7290294
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG binding proteins in the nervous system

Abstract: Classical methyl-CpG binding proteins contain the conserved DNA binding motif methyl-cytosine binding domain (MBD), which preferentially binds to methylated CpG dinucleotides. These proteins serve as transcriptional repressors, mediating gene silencing via DNA cytosine methylation. Mutations in methyl-CpG binding protein 2 (MeCP2) have been linked to the human mental retardation disorder Rett syndrome, suggesting an important role for methyl-CpG binding proteins in brain development and function. This mini-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 67 publications
(112 reference statements)
1
58
0
2
Order By: Relevance
“…However, we cannot rule out the possible involvement of other methyl binding proteins (e.g. MBD1-3) in the nervous system for their potential role in glial gene silencing during early CNS development (Heinrich and Bird, 1998) (reviewed by Fan and Hutnick, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot rule out the possible involvement of other methyl binding proteins (e.g. MBD1-3) in the nervous system for their potential role in glial gene silencing during early CNS development (Heinrich and Bird, 1998) (reviewed by Fan and Hutnick, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the interesting possibility that a reduction in Freud-1-mediated repression of the DRD2 gene may contribute to the mental retardation phenotype or to other developmental disorders in which dysregulation of the dopamine system is implicated, such as attention deficit hyperactivity disorder, autism, or schizophrenia (25). In some cases mental retardation has been linked to global regulators of gene transcription, such as the ATPase/helicase ATRX (alpha thalassemia/mental retardation syndrome X-linked) (43,44) or the methyl binding repressor methyl CpG-binding protein 2 (45,46). Likewise, Freud-1 may regulate other genes in addition to 5-HT1A or dopamine-D2 receptor genes to regulate cognitive development.…”
Section: Freud-1 Mediated Repression Of the Dopamine-d2mentioning
confidence: 99%
“…Recently, studies have suggested a relationship between RTT and MECP2 in the regulation of UBE3A (Ubiquitin-Protein ligase E3A), GABRB3 (the beta3 subunit of the GABAA receptor) and CDKL5 (Cyclin-dependent kinase-like5) expression (Fan G and Hutnick L, 2005;Milani et al, 2005;Samaco et al, 2005;Segawa and Nomura, 2005). In this study, we did not detect any mutations of MECP2 in seventeen of the patients.…”
Section: Discussionmentioning
confidence: 58%